2023
DOI: 10.5114/ceh.2023.124476
|View full text |Cite
|
Sign up to set email alerts
|

Is the extent of functional liver remnant increase truly “functional”? A single-institution case series of patients with associating liver partition and portal vein ligation for staged hepatectomy (ALPPS)

Abstract: Introduction: Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS) aims to induce rapid hypertrophy of the future liver remnant (FLR) to reduce the risk of post-hepatectomy liver failure (PHLF). However, volumetric increase does not correspond to functional increase. This is a novel study which aims to compare the increase in standardized FLR (sFLR) vs. indocyanine green retention at 15 minutes (ICG-R15). Material and methods: This is a retrospective case series of patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…A study by Schwarz et al [ 37 ] comprising 698 patients similarly showed that patients with impaired ICG clearance were twice as likely to have postoperative liver dysfunction. A recent retrospective study however highlighted that in patients treated with associating liver partition and portal vein ligation for staged hepatectomy, ICG-R15 overestimated the true liver function increase post-operatively[ 41 ]. These results remain to be validated, and are essential in tailoring treatment to prevent PHLF.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Schwarz et al [ 37 ] comprising 698 patients similarly showed that patients with impaired ICG clearance were twice as likely to have postoperative liver dysfunction. A recent retrospective study however highlighted that in patients treated with associating liver partition and portal vein ligation for staged hepatectomy, ICG-R15 overestimated the true liver function increase post-operatively[ 41 ]. These results remain to be validated, and are essential in tailoring treatment to prevent PHLF.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the function of the hypertrophied FLR was questioned (27). Studies using hepatobiliary scintigraphy (41), LIMAx test (42) and indocyanine green retention test (43) resulted in the same conclusion: the increase in FLR volume is not followed by a proportional increase in liver function. Thus, it is advocated by some authors to consider using these tests to evaluate FLR function before proceeding with the second stage of ALPPS.…”
Section: Discussionmentioning
confidence: 99%
“…While these modalities are attractive, they also do not eliminate PHLF risk. For example, a local audit of 10 ALPPS patients revealed that volumetric increase does not correspond to liver function enhancement and one patient developed PHLF ( 13 ).…”
mentioning
confidence: 99%